Significance of Electronic Picture Story Book in TEYL - Tiray Febria Zananda (Universitas Indo Global Mandiri, 2020)
ABSTRACTIn this digital era, the product of technology such as tablet PC, iPad, Smartphone, computer, internet access and electronic book reader are close in our daily life. This article highlights the benefit of using electronic picture story book. Electronic picture story book is one of the tools that can be used in teaching reading for young learners in the literacy activity. It is development of modern education which integrates with technology. Electronic picture story book can be helpful as a supplement to the language.Young learners have their own perspective in comprehending a message. They have different way to transfer what they have in their mind. By having visualization, young learners will more enthusiastic and interested to read in order to get good stimulation through their imaginations. Electronic picture story book could be considered an aggregation of multi-pages, responsive and lively multi-media (includes information of characters, picture, voice , sounds effects, music, animation, etc). Visual aids in electronic picture story book are helpful for getting the information and mental representation. Electronic picture story book could become innovative and creative as their guide in the literacy activity. This article offers the potential ways to build children’ reading enthusiasm through electronic picture book.Keywords : Electronic picture story book, readingABSTRAKDi era digital ini, produk teknologi seperti PC tablet, iPad, Smartphone, komputer, akses internet, dan pembaca buku elektronik sangat dekat dalam kehidupan kita sehari-hari. Artikel ini memberikan manfaat menggunakan buku cerita bergambar elektronik. Buku cerita bergambar elektronik adalah salah satu alat yang dapat digunakan dalam pengajaran membaca untuk pelajar muda dalam kegiatan literasi. Ini adalah pengembangan pendidikan modern yang terintegrasi dengan teknologi. Buku cerita bergambar elektronik dapat membantu sebagai pelengkap bahasa. Pembelajar muda memiliki perspektif mereka sendiri dalam memahami pesan. Mereka memiliki cara berbeda untuk mentransfer apa yang ada dalam pikiran mereka. Dengan memiliki visualisasi, pembelajar muda akan lebih antusias dan tertarik membaca untuk mendapatkan stimulasi yang baik melalui imajinasi mereka. Buku cerita bergambar elektronik dapat dianggap sebagai kumpulan multi-halaman, multi-media yang responsif dan hidup (termasuk informasi karakter, gambar, suara, efek suara, musik, animasi, dll). Bantuan visual dalam buku cerita bergambar elektronik sangat membantu untuk mendapatkan informasi dan representasi mental. Buku cerita bergambar elektronik bisa menjadi sesuatu yang inovatif dan kreatif sebagai panduan mereka dalam kegiatan literasi. Artikel ini menawarkan cara-cara potensial untuk membangun antusiasme membaca anak-anak melalui buku bergambar elektronik.Kata kunci : Buku cerita bergambar elektronik, keterampilan membaca